2011
DOI: 10.1111/j.1365-2826.2011.02184.x
|View full text |Cite
|
Sign up to set email alerts
|

A Bold View of the Lactating Brain: Functional Magnetic Resonance Imaging Studies of Suckling in Awake Dams

Abstract: Functional magnetic resonance imaging (fMRI) has been used to investigate the responsiveness of the maternal rat brain to pup‐suckling under various experimental paradigms. Our research employing the lactating rat model has explored the cortical sensory processing of pup stimuli and the effect of suckling on the brain’s reward system. Suckling was observed to increase blood‐oxygen‐level‐dependent (BOLD) signal intensity in the midbrain, striatum and prefrontal cortex, which are areas that receive prominent dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 101 publications
(167 reference statements)
0
21
0
Order By: Relevance
“…Non-maternal animals, such as fathers or any older conspecific animals, might provide maternal-like care to the young using behaviors collectively designated as parental behavior. Although several brain areas are important for different parental behavior components (Febo, 2011;Pereira and Morrell, 2011;Stolzenberg and Numan, 2011), the medial preoptic area (MPOA) has been shown to be the most critical, especially for pup retrieval, as shown by the following four lines of evidence: first, destruction of MPOA with either electrical or excitotoxic lesions disrupts both established maternal behavior in postpartum females (Numan, 1974;Jacobson et al, 1980;Numan et al, 1988) and the onset of parental behavior in adult females (Numan et al, 1977;Fleming et al, 1983), adult males, and juveniles (Rosenblatt et al, 1996;Sturgis and Bridges, 1997;Kalinichev et al, 2000;Oxley and Fleming, 2000;Lee and Brown, 2002). Knife cuts of dorsolateral connections of the MPOA also abolish the maternal behavior of postpartum rats (Terkel et al, 1979;Numan and Callahan, 1980;Numan et al, 1990) and hamsters (Miceli and Malsbury, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Non-maternal animals, such as fathers or any older conspecific animals, might provide maternal-like care to the young using behaviors collectively designated as parental behavior. Although several brain areas are important for different parental behavior components (Febo, 2011;Pereira and Morrell, 2011;Stolzenberg and Numan, 2011), the medial preoptic area (MPOA) has been shown to be the most critical, especially for pup retrieval, as shown by the following four lines of evidence: first, destruction of MPOA with either electrical or excitotoxic lesions disrupts both established maternal behavior in postpartum females (Numan, 1974;Jacobson et al, 1980;Numan et al, 1988) and the onset of parental behavior in adult females (Numan et al, 1977;Fleming et al, 1983), adult males, and juveniles (Rosenblatt et al, 1996;Sturgis and Bridges, 1997;Kalinichev et al, 2000;Oxley and Fleming, 2000;Lee and Brown, 2002). Knife cuts of dorsolateral connections of the MPOA also abolish the maternal behavior of postpartum rats (Terkel et al, 1979;Numan and Callahan, 1980;Numan et al, 1990) and hamsters (Miceli and Malsbury, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Delayed response cells have been described in working memory tasks in the rat. Information processed during such a firing pattern is perhaps incorporated into working memory (Jung et al, 1998) or conveyed to other subcortical areas such as the dorsal striatum (Febo, 2011). Other work has shown that delayed response neurons fire when a sequence of stimuli predictive of a reward are presented (Cowen and McNaughton, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Offspring are highly rewarding and previous studies have demonstrated alterations in reward systems in the maternal brain (Wilsoncroft, 1968; Hauser and Gandelman, 1985; Lee et al, 1999; Mattson et al, 2001, 2003; Febo et al, 2005; Ferris et al, 2005; Mattson and Morrell, 2005; Seip and Morrell, 2007; Noriuchi et al, 2008; Strathearn et al, 2008; Febo, 2011). For example, naïve prepartum female rodents find social interactions with mouse pups to have low valence (Lonstein and De Vries, 2000), but postpartum females find social interactions with pups to be intensely rewarding (Hauser and Gandelman, 1985).…”
Section: Bonding Reward and Addiction Pathways In The Postpartummentioning
confidence: 99%